Efficacy and Tolerability of Phototherapy With Light-Emitting Diodes for Sensitive Skin: A Pilot Study - Sonbol, Haitham; Brenaut, Emilie; Nowak, Emmanuel; Misery, Laurent (Frontiers in Medicine, 2020)
Sensitive skin (SS) syndrome is defined by the occurrence of unpleasant sensations in response to stimuli that should normally not induce such sensations. It affects approximately 50% of women and 40% of men and can impact the quality of life. There is no consensus on therapeutic management. Phototherapy by light-emitting diodes (LEDs) is increasingly being used in dermatology for various inflammatory skin disorders with significant reduction in SS-10 and good tolerability. A Korean study suggested its efficacy in alleviating SS symptoms associated with other facial diseases. Our objective is to obtain preliminary data on the efficacy of phototherapy with LEDs for alleviating SS symptoms and increasing tolerance in subjects with SS that is not associated with other facial skin disorders. This monocentric pilot study included 30 subjects with SS who had a Sensitive Scale-10 score ≥40. The treatment consisted of red LED light exposure twice a week until significant reduction in SS-10 with a maximal treatment length of 8 weeks. The primary outcome was defined by a 60% decrease in the SS-10 score compared to the baseline. Results: Thirty subjects were included; 83% were women, and the mean age was 28.9 years. Two participants were considered lost to follow-up. The cheeks (90%) and the nose (70%) were the most frequently involved parts of the face. Cold, heat, temperature variation, water and sun were the most frequent triggering factors. Twenty-eight subjects (93.3%, 95% CI 77.9 to 99.2%) achieved the primary outcome. Significant reduction in SS-10 was achieved in 77% of subjects in 6 sessions or fewer. The mean (SD) SS-10 scores were 54.7 (12.1) at inclusion, 14.4 (6.0) at the last session and 13.9 (7.5) 2 months after the last session, suggesting that the benefits persist for a few weeks. Two side effects were reported: both were allergic reactions to the nickel contained in the protective goggles. This pilot study had a small sample size and no control group. LEDs were effective in treating SS in all 28 subjects who completed the study in accordance with the protocol, and the benefits persisted for 2 months after the last LED therapy session.